Critical issues facing the Middle East : security, politics, and economics - Russell, James A. (James Avery), 1958- (Initiatives in strategic studies--issues and policies., 2006)
Addressing systemic changes in the Middle East's security environment since the Iraq War, prominent experts analyze the challenges these changes pose to US strategy and policy. They examine the causes of profound economic, political and religious transitions and their implications for hopes of reform.